NILAI NILAI KEHIDUPAN REMAJA DI LINGKUNGAN BELAJAR DALAM EPOS ITIHASA MAHABHARATA DAN RAMAYANA - arsa antara, i putu puja (UHN IGB Sugriwa Denpasar, 2026)
Itihasa, which includes great Ramayana and Mahabharata epic, has a deep moral, spiritual, and education that remains relevant in modern life. This epic presents universal teachings of truth, liabilities, justice, and devotion that can guide human behavior and character development. In the field of education, values found in Itihasa such as discipline, loyalty, respect to teachers, and knowledge chase plays a crucial role in shaping students’ moral awareness and decision making. Through characters like Rama, Sita, Arjuna, and Krishna, students can explore examples of integrity, perseverance, and struggle between good and evil. Integrating Itihasa's value into education encourages holistic learning that maintains intelligence and spirituality. This helps students understand that education is not only about academic performance but also about the growth of noble character formation and a harmonious relationship with others and their environment. Therefore, implementing Itihasa teachings in modern education contributes to creating a wise young generation, and spiritually balanced, can face global challenges while maintaining cultural identity and integrity.